Atrial Pacing Negatively Affects Left Atrial Morphological and Functional Parameters Similarly to Atrioventricular Dyssynchrony - Viezelis, Mindaugas; Neverauskaite-Piliponiene, Gintare; Marcinkeviciene, Agne; Kazakevicius, Tomas; Zabiela, Vytautas; Kviesulaitis, Vilius; Jurkevicius, Renaldas; Puodziukynas, Aras (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Atrioventricular (AV) dyssynchrony as well as atrial and ventricular pacing affect left atrial (LA) function. We conducted a study evaluating the effect of atrial and ventricular pacing on LA morphological and functional changes after dual-chamber pacemaker implantation. Materials and Methods: The study prospectively enrolled 121 subjects who had a dual-chamber pacemaker implanted due to sinus node disease (SND) or atrioventricular block (AVB). Subjects were divided into three groups based on indication and pacemaker programming: (1) SND DDDR 60; (2) AVB DDD 60 and (3) AVB DDD 40. Subjects were invited to one- and three-month follow-up visits. Three subsets based on pacing burden were analyzed: (1) high atrial (A) low ventricular (V); (2) high A, high V and (3) low A, high V. LA function was assessed from volumetric parameters and measured strains from echocardiography. Results: The high A, low V group consisted of 38 subjects; while high A, high V had 26 and low A, high V had 23. A significant decrease in reservoir and contractile LA strain parameters were only observed in the high A, low V pacing group after three months (reservoir 25.9 ± 10.3% vs. 21.1 ± 9.9%, p = 0.003, contractile −14.0 ± 9.0% vs. −11.1 ± 7.8, p = 0.018). While the re-established atrioventricular synchrony in the low A, high V group maintained reservoir LA strain at the baseline level after three months (21.4 ± 10.4% vs. 22.5 ± 10.4%, p = 0.975); in the high A, high V group, a further trend to decrease was noted (20.3 ± 8.9% vs. 18.7 ± 8.3%, p = 0.231). Conclusions: High atrial pacing burden independently of atrioventricular dyssynchrony and ventricular pacing impairs LA functional and morphological parameters. Changes appear soon after pacemaker implantation and are maintained.